PENGEMBANGAN INSTRUMEN TES UNTUK MENGUKUR KEMAMPUAN BERPIKIR TINGKAT TINGGI PADA MATA PELAJARAN MATEMATIKA SEKOLAH DASAR - Gadis Niyanti Pertiwi; Nuryani, Nuryani; Edi Rohyadi; Yuyu Yuhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to produce a test instrument to measure students' higher order thinking skills in the field of mathematics to produce a test instrument to measure problem solving skills by looking at the development procedure and the quality of the developed mathematical problem solving test instrument. The type of research used is the development of test instruments to measure mathematical problem solving skills. The test subjects in this study were fifth grade students of Banjar Agung 2 State Elementary School, Serang City, totaling 30 students. Based on the results of the trials conducted, it was found that: (1) the math problem solving test instrument has been said to be "valid" because based on the CVR results, namely 1 and meets the criteria, namely ≥0.99 and CVI, namely 1 with a very suitable category or is in the range of 0.68-1.00 (2) the math problem solving test instrument has been said to be reliable with a value of 0.76 with a high category, and is in the range of 0.60 <r11<0, 80 (3) the math problem solving test instrument has a fairly good difficulty level, namely 50% of the questions have a good difficulty level then the average difficulty level obtained is 0.59 with a moderate category, which is in the range of 0.31-0.70 (4) the math problem solving test instrument has a good differentiating power 100% of the questions meet the criteria for differentiating power and the average differentiating power obtained is 0.38 with a sufficient category or in the range Dp>0.2. Thus the math problem solving test instrument in the form of High Order Thinking Skill has good quality.